2022
DOI: 10.21107/prosodi.v16i1.13456
|View full text |Cite
|
Sign up to set email alerts
|

Students’ Perception of Listening Material in Extensive Listening

Abstract: Extensive listening takes an essential role in improving students’ listening skill. Extensive listening provides or promote students’ comprehension and enjoyment in class activity or listening practices. The success of extensive listening is depended on having easy the access of right materials. The present study examines on students’ perception of listening material in extensive listening. The present study only focuses on the materials are designed for some meeting in extensive listening class. In this regar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…We could not have asked them to listen any faster, but what we can do is give them repeated listening practice so that they gradually become accustomed to listening to normal speech. This is also in line with the results of Kristanti & Ni'amah (2022), which states that Extensive Listening can explore students abilities regarding normal speech rate. Waring (2010) also stated that extensive listening is an approach to improve students' listening fluency.…”
Section: Finding and Discussionsupporting
confidence: 89%
“…We could not have asked them to listen any faster, but what we can do is give them repeated listening practice so that they gradually become accustomed to listening to normal speech. This is also in line with the results of Kristanti & Ni'amah (2022), which states that Extensive Listening can explore students abilities regarding normal speech rate. Waring (2010) also stated that extensive listening is an approach to improve students' listening fluency.…”
Section: Finding and Discussionsupporting
confidence: 89%
“…It is noted that students are more aware of the influences of the listening practices towards not only their language development but also their overall understanding of the topic they listened to, confirming their believe, enhancing their current level of comprehension, boosting their curiosity, and encouraging positive attitude. In line with this, it was also found that students engaging in extensive listening activities are motivated in practicing listening because they could choose the materials that they like and gain knowledge on the topic they chose as well as increasing word recognition in normal speech (Kristanti, Ni'amah, 2022). This also corresponds to the believes that learning materials are supposed to induce students' curiosity and interest in foreign language as well as support their knowledge and language development, while instilling poritive attitude towards language learning (Usaquén, 2012;Hanifa and Yusra, 2023).…”
Section: Excerpt 7: "Overall I Am Satisfied With This Video But the C...mentioning
confidence: 71%